Aspects of rendering the sacred Tetragrammaton in Greek - Vasileiadis, Pavlos D. (Open theology, 2015)
This article recounts the persistent use of the sacred Tetragrammaton through the centuries as an "effable," utterable name at least in some circles, despite the religious inhibitions against its pronunciation. A more systematic investigation of the various Greek renderings of the biblical name of God is provided. These renderings are found in amulets, inscriptions, literary works, etc., dating from the last few centuries B.C.E. until today. It will be illustrated that some forms of the Tetragrammaton were actually accepted and used more widely within the Greek religious and secular literature since the Renaissance and especially since the Modern Greek Enlightenment. Furthermore, it is asserted that for various reasons there is no unique or universally "correct" rendering of the Hebrew term in Greek. Of special note are two Greek transcriptions of the Tetragrammaton, one as it was audible and written down by a Greek-speaking author of a contra Judaeos work in the early 13th century in South Italy and another one written down at Constantinople in the early 17th century—both of them presented for the first time in the pertinent bibliography.